From Tradition to Innovation: The Role of Tasar Sericulture and PRADAN in Shaping Rural Entrepreneurship in Jharkhand, India - Rinki Kumari (New Advances in Business, Management and Economics Vol. 3, 2025)
India produces all four varieties of silk, including Mulberry, Tasar, Muga, and Eri. Vanya Silk among the various forms of silk produced, Tasar silk holds a special place. Tasar sericulture in India, particularly in states like Jharkhand, carries deep cultural significance and substantial potential for rural entrepreneurship and socio-economic development. As the world’s second-largest producer of raw silk, India contributed 34,903 metric tons in 2021-22, with tasar silk constituting 4% of the country’s total silk exports, producing 1,466 metric tons. This sector employs rural communities extensively, with 76.4% of Tasar silk originating in Jharkhand. Despite its potential, Tasar sericulture faces several challenges. These include a critical shortage of disease-free tasar moth eggs (disease-free layings or DFLs), the sector struggles with outdated technologies, inadequate marketing connections, and a conventional value chain that limits entrepreneurial opportunities for producers. NGOs like PRADAN, in collaboration with government bodies such as the Central Silk Board, play a crucial role in empowering marginalized groups and fostering entrepreneurship. PRADAN played a pivotal role in establishing the Tasar Development Foundation (TDF) in 2013 to foster the expansion of the Tasar subsector. This extension is helpful to the scientific community because this will help to easily assess the production data. This paper aims to highlight the significant impact of Tasar sericulture and the endeavours of the PRADAN organization in empowering rural entrepreneurs in the state of Jharkhand, India. This study also assesses and showcases the impact of the PRADAN Organisation’s initiatives and Interventions in empowering marginalised communities in collaboration with CSB through entrepreneurship, and socio-economic development programs. Both the Qualitative and Quantitative data have been collected and analysed. Despite challenges, the tasar silk industry showcases resilience and adaptability. With continued support and innovation, this industry contributes to India’s tradition of silk production and the uplifting of rural communities.